LEVEL OF GENERIC SKILLS REQUIREMENT AMONG TECHNICIAN IN POLYTECHNIC - Esa, Ahmad Bin; Abd Hadi, Moh Yusof Bin; Ishak, Fariza Binti; Salleh, Burhannudin Bin Mohd (International Journal of Education, 2012)
Generic skills are important skills for worker that required by almost of the employments.  Beside technical skills, generic skills are designed for employee in order to produce excellent and efficient job.  This research is focus on to identify the level of generic skills desirable by technician and the level of skills that they have from lecturer, student and technician perspective in polytechnic. The total of research respondent is 366 which consist of lecturers, students and technicians. The data is collected from questionnaire and analyzed by SPSS v.12 programmer to get mean score, standard deviation, factor analysis and ANOVA testing.  Research finding found that the level of generic skills requirement among the technician is at a higher level (mean=4.156) and also mastering in generic skills at the higher level too (mean=4.184). Mean while, by the ANOVA analysis it is found that there is a significant different on generic skills technician level of requirement among the polytechnic. Through factor analysis, it is found nine (9) of generic skills are imperative to equip by technician. Based on research finding, hopefully a significant authority board will take a move to increase the generic skills among technician and other staffs in polytechnic. Keyword. Generic Skills, Technician and Polytechnic